Antepartum multidisciplinary approach improves postpartum pain scores in patients with opioid use disorder - Yang, Tiffany; Stetler, Emily; Garretto, Diana; Herrera, Kimberly; Garry, David; Heiselman, Cassandra (Journal of perinatal medicine, 2025)
Pregnancies affected by opioid use disorder (OUD) face difficulties with postpartum pain control. This study aims to determine if prenatal anesthesia consultation for patients on medication for opioid use disorder (MOUD) affects maternal postpartum pain control. This is a retrospective cohort study of pregnant patients diagnosed on MOUD who received prenatal care and delivered at a single academic institution between January 2017 and July 2023. Subjects were divided into those who received prenatal anesthesia consultation and those who did not. Severe pain (numerical rating scale 0-10) was defined as score≥7. Statistical analysis was performed using Chi-square, Mann-Whitney U, and multivariable logistical regression tests with significance defined as p<0.05. The cohort included 359 women on MOUD. Of these, 17.8 % (n=64) received anesthesia consultation and 82.2 % (n=295) did not. Factors found associated with receiving anesthesia consultation were prenatal care with an obstetric provider trained in maternal OUD (p<0.01), psychiatric diagnosis (p<0.01) and higher number of prenatal care visits (10.12 vs. 8.99, p=0.007). When comparing pain scores in the first 24 h postpartum, patients with prenatal anesthesia consultation had statistically significant lower rates of severe pain compared to those who did not (25 vs. 44.7 %, p=0.004). Anesthesia consultation (OR 0.34) and cesarean section (OR 2.81) were independent predictors of severe postpartum pain in the first 24 h after delivery. Patients on MOUD who received antenatal anesthesia consultation report lower postpartum pain scores than those without consultation, which supports that multidisciplinary care for pregnant patients with OUD may help the postpartum experience.